Peran Pola Asuh Orang Tua dalam Mencegah Perilaku Kenakalan Remaja - Wasilah, Nil (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Juvenile delinquency can be described as a failure to fulfill developmental tasks. Some teenagers fail to develop the self-control that other teenagers their age already have during development. Success in fulfilling developmental tasks makes teenagers aware and sensitive to norms, so that teenagers are able to resist the urge for self-gratification so as not to violate applicable norms and rules. On the other hand, failure in this developmental task will cause adolescent individuals to become less sensitive to applicable norms and rules. This causes adolescent individuals to become vulnerable to behavior that violates the rules and even commits criminal acts. So, during the adolescent development stage, parents play a major role in implementing appropriate parenting patterns in preventing juvenile delinquent behavior. This research uses a descriptive qualitative research method by searching for sources of information as deeply as possible from sources or respondents using data collection techniques in the form of interviews, observation and documentation.